1989
DOI: 10.3758/bf03208149
|View full text |Cite
|
Sign up to set email alerts
|

Further experiments on the perception of growth in three dimensions

Abstract: Mark and Todd (1983) reported an experiment in which the cardioidal strain transformation was extended to three dimensions and applied to a three·dimensiona1 (3·D) representation of the head of a 15·year-old girl in a direction that made the transformed head appear younger to the vast majority of their subjects. The experiments reported here extend this research in order to examine whether subjects are indeed detecting cardioidal strain in three dimensions, rather than detecting changes in head slant or making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…If subjects are forced to use only one cue because only one is available (such as cardioidal strain or skin texture) it is still possible for them to make reasonably accurate age judgments but, in practice, cues to age are probably normally used in combination. This reinforces the conclusions drawn by Bruce et al (1989), who found that providing subjects with a richer database on which to base their age judgments (computer-generated 3-D head models) led to poorer and more idiosyncratic performance than that found by Mark and Todd (1985) who used simple line drawings of head profiles.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…If subjects are forced to use only one cue because only one is available (such as cardioidal strain or skin texture) it is still possible for them to make reasonably accurate age judgments but, in practice, cues to age are probably normally used in combination. This reinforces the conclusions drawn by Bruce et al (1989), who found that providing subjects with a richer database on which to base their age judgments (computer-generated 3-D head models) led to poorer and more idiosyncratic performance than that found by Mark and Todd (1985) who used simple line drawings of head profiles.…”
Section: Discussionsupporting
confidence: 70%
“…For example, Mark and Todd (1985) and Bruce et al (1989) obtained their data by presenting subjects with stimuli in pairs and asking them to decide which of each pair looked 'older'. Measures like this provide information about relative-age judgments, but would have been too crude for our purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Pittenger, Shaw, Mark, and their colleagues (eg Pittenger and Shaw 1975;Pittenger et al 1979;Mark and Todd 1985; see also Bruce et al 1989) have shown that changes in the shape of the skull during growth can be modelled by a mathematical transformation called cardioidal strain. These researchers suggest that sensitivity to the level of cardioidal strain underlies judgments of facial age.…”
Section: Introductionmentioning
confidence: 99%
“…D'Arcy Thompson [6] suggested that it is possible to use co-ordinate transformations for altering the shape of biological organisms in order to produce shapes belonging to different but similar biological organisms. Based on this idea a number of researchers [1,19,20] investigated the use of co-ordinate transformations in an attempt to impose age-related changes on human faces. According to their experimental evaluations the perceived age of transformed facial outlines can be altered according to the transformation factors used.…”
Section: Literature Reviewmentioning
confidence: 99%